An Analysis of Concentration Region on Powerpoint Slides using Eye Tracking - Fergyanto E. Gunawana; Oky Wijaya; Benfano Soewito; Sevenpri Candra; Diana Diana; Cosmas E. Suharyanto (IAES Indonesia Section, 2017)
Powerpoint slides have become one of the essential teaching tools in academic for both offline and online modes. It may play a useful role to facilitate discussion and information exchange. However, in our teaching experience, we find many students utilizing Powerpoint slides beyond their traditional functions. Many students fully rely on the slides as the main learning materials and, in some cases, substituting textbooks. This study intends to understand how students interact with the learning materials presented on Powerpoint slides. The interaction is measured using an eye tracker device called the Eye Tribe Tracker. Thirty sophomore and junior students are asked to participate. They are instructed to learn a topic in the subject of Introduction to Algorithm and Programming, a basic course in the computer science field. During the process, their fixation points are monitored and are related to the contents on the slides. The results are rather surprising. Many students read the slides in unexpected manners that may compromise their understanding and may lead to inaccurate interpretations.